ELASTIC SCATTERING ANGULAR DISTRIBUTION DEUTRONS WITH E=18 MeV AND ALPHA-PARTICLES WITH E = 5.5 MeV AT 9-Be, 10-B, 11-B, 13-C, 24-Mg,25-Mg, 27-Al - Dyachkov, V.V.; Burtebaev, N.T.; Shakirov, A.L.; Yushkov, A.V. (Recent Contributions to Physics, 2018)
Developed high-precision technique for measuring the angular distributions of differential cross sections for elastic scattering of charged particles using a position-sensitive solid-track detectors. Measured the differential cross sections for the reaction 27Al(a,a)27Al at energies of alpha particles 5.5 MeV. Measured the semiconductor technique at the isochronous cyclotron U-150M angular distributions of deuterons with energy 18 MeV in 9-Be, 10-B, 11-B, 1913-C, 24-Mg ,25-Mg and theoretically treated by the model of the method of complex angular moments (MKUM).